SEED AND OIL YIELDS OF RAPESEED (BRASSICA NAPUS L.) CULTIVARS UNDER IRRIGATED AND NON-IRRIGATED CONDITIONS - A. H. S. Rad; A. Abbasian; H. Aminpanah (Journal of Animal and Plant Sciences, 2014)
Drought is the major factor limiting plant growth and productivity in many regions of the world more than any other environmental factors. To determine the effect of water deficit on seed and oil yields in rapeseed (Brassica napus L.) cultivars, field experiments were conducted at the Seed and Plant Improvement Institute, Karaj, Iran, during 2007–2009. The experimental designs were randomized complete block with split-plot arrangement and three replicates. main plots were four levels of irrigation (control (irrigation after 80 mm evaporation from class “A” pan , IR1), no irrigation after the start of stem elongation stage (IR2), no irrigation after the start of flowering stage (IR3), and no irrigation after the start of podding stage (IR4)), and subplots were six rapeseed cultivars (Licord, SLM046, Okapi, Orient, Zarfam and Opera). Results showed that seed and oil yields, number of pods per plant, and number of seeds per pod were significantly affected by year, rapeseed cultivar and irrigation level. Moreover, the most average yield reduction due to drought conditions (IR2) in comparison with control (IR1) in first and second year was 30.44% (Licord) and 50.27% (Zarfam), respectively. In both two years, SLM046 cultivar has the least percentage of yield reduction and it was the best yielding in water stress conditions. Therefore, these experiments illustrated that rapeseed cultivars showed significantly different responses, depending on weather conditions, to different irrigation levels and SLM046 cultivar showed higher ability to capture soil moisture under severe competition and had the least reduction in seed yield compared to the other cultivars.
Keywords: Brassica napus L.; oil yield; seed yield; water deficit; winter rapeseed cultivars